Toll-like receptor 4 and Syk kinase shape dendritic cell-induced immune activation to major house dust mite allergens - Busold, Stefanie; Akkerdaas, Jaap H.; Zijlstra-Willems, Esther M.; van der Graaf, Kees; Tas, Sander W.; de Jong, Esther C.; van Ree, Ronald; Geijtenbeek, Teunis B. H. (Frontiers in Medicine, 2023)
Background: House dust mite (HDM) is a major cause of respiratory allergic diseases. Dendritic cells (DCs) play a central role in orchestrating adaptive allergic immune responses. However, it remains unclear how DCs become activated by HDM. Biochemical functions of the major HDM allergens Der p 1 (cysteine protease) and Der p 2 (MD2-mimick) have been implicated to contribute to DC activation. Methods: We investigated the immune activating potential of HDM extract and its major allergens Der p 1 and Der p 2 using monocyte-derived DCs (moDCs). Maturation and activation markers were monitored by flow cytometry and cytokine production by ELISA. Der p 1 depletion and proteinase K digestion were used to investigate the involvement of proteins, and in particular of the major allergens. Inhibitors of Toll-like receptor 4 (TLR4) and of C-type lectin receptors (CLRs) were used to identify the involved receptors. Results: HDM extract induced DC maturation and cytokine responses in contrast to the natural purified major allergens Der p 1 and Der p 2. Proteinase K digestion and removal of Der p 1 did not alter the immune stimulatory capacity of HDM extract. Blocking TLR4 signalling reduced the HDM-induced IL-10 and IL-12p70 induction, but not IL-6. In contrast, antibodies against the CLRs Dectin-1, Dectin-2, and DC-SIGN did not affect cytokine responses. Strikingly, spleen tyrosine kinase (Syk) inhibition partially reduced IL-6, IL-12 and completely blocked IL-10. Conclusion: Our data strongly suggest that HDM-induced immunity is neither dependent on Der p 1 nor Der p 2, but depends on Syk and TLR4 activation, suggesting crosstalk between Syk and TLR4 pathways. Our data further indicate that a Syk-dependent receptor other than Dectin-1 and Dectin-2 might be involved in immune activation by HDM.